1998
DOI: 10.1074/jbc.273.42.27686
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Cyclooxygenase-2 in Mouse Skin Carcinoma Cells

Abstract: Many studies have suggested that overexpression of cyclooxygenase-2 (COX-2) contributes to the development of tumors in several tissues. COX-2 expression tends to be up-regulated in various types of tumors and transformed cell lines, and the overexpression of COX-2 is caused by enhanced transcription of the gene. In an attempt to characterize the signaling pathway leading to the overexpression of COX-2 in the mouse skin carcinoma cell line JWF2, we investigated cis-and transacting factors required for COX-2 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(87 citation statements)
references
References 62 publications
(68 reference statements)
3
84
0
Order By: Relevance
“…The transcription factor C/EBP␤ is known to play a role in the activation of the COX-2 gene (14), and LPS was reported to increase the level of C/EBP␤ in RAW264.7 and J774 macrophages by stimulating transcription of the gene (15). We confirmed that LPS induces a striking rise in the level of C/EBP␤, and we also found that this increase was not prevented by SB 203580 and/or PD 98059 or by Ro 318220 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor C/EBP␤ is known to play a role in the activation of the COX-2 gene (14), and LPS was reported to increase the level of C/EBP␤ in RAW264.7 and J774 macrophages by stimulating transcription of the gene (15). We confirmed that LPS induces a striking rise in the level of C/EBP␤, and we also found that this increase was not prevented by SB 203580 and/or PD 98059 or by Ro 318220 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors belonging to the C/EBP family share a strong homology in their leucine zipper and DNA binding domains, and as a consequence are able to form both homo-and heterodimers and bind to the same DNA sequences (22). Different C/EBP family members can bind to the Ϫ138/Ϫ130 element, but their relative role in activating the cox-2 promoter in different cell types is unclear and sometimes contradictory (9,10,12,17,20,23). However, all these studies are based on transient transfection/overexpression experiments and do not take into account the endogenous and regulated ratio of C/EBP family members able to bind to the promoter under uninduced or induced conditions.…”
Section: Prostaglandins (Pg)mentioning
confidence: 99%
“…Interestingly, whereas in macrophages and fibroblasts the CRE moiety is responsible for transcriptional activation by members of the CRE-binding protein (CREB) and activating protein-1 (AP-1) family (12,15), in rat granulosa and skin carcinoma cells the E box is predominantly involved through the interaction with the upstream stimulating factors 1 and 2 (16,17). Finally, the nuclear factor for IL-6/CCAAT enhancer-binding protein (NF-IL6/C/EBP) element at position Ϫ138/Ϫ130 was reported to play an important role in mediating signal-dependent transcriptional induction in macrophages, osteoblastic cells, pancreatic islet cells, skin carcinoma cells, and chondrocytes (6,9,10,12,13,17,18,20) but not in rat granulosa cells or in fibroblasts (15,16). Transcription factors belonging to the C/EBP family share a strong homology in their leucine zipper and DNA binding domains, and as a consequence are able to form both homo-and heterodimers and bind to the same DNA sequences (22).…”
Section: Prostaglandins (Pg)mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the high degree of conservation in their bZIP domains, C/EBP family members form both homodimers and heterodimers (Rask et al, 2000). C/EBPd, another member of the C/EBP family, is upregulated in mouse skin papillomas and squamous cell carcinomas (Kim and Fischer, 1998). On the other hand, C/EBPd might act as a tumor suppressor by virtue of its role in genome maintenance (Huang et al, 2004).…”
mentioning
confidence: 99%